The link between information and digital technologies of industry 4.0 and agile supply chain: Mapping current research and establishing new research avenues. (May 2022) - Oliveira-Dias, Diéssica; Maqueira-Marín, Juan M.; Moyano-Fuentes, José
Highlights: Systematic review of 123 papers about IDT of Industry 4.0 (I4.0) and Agile Supply Chain (ASC) Develops a novel literature classification based on the Technology Life Cycle. Presents a comprehensive overview of the state-of-knowledge on IDT of I4.0 and ASC. Presents an ASC model enabled by IDT of I4.0. Derives gaps and promising ideas for future research on IDT of I4.0 and ASC. Abstract: The use of Industry 4.0 (I4.0) Information and Digital Technologies (IDT) has given rise to new opportunities and challenges for designing and managing agile supply chains. Therefore, this study aims to investigate the role and implications of IDT of I4.0 for the Agile Supply Chain (ASC) strategy through a systematic literature review of 123 identified papers. The literature has been classified into three research lines based on the Technology Life Cycle: (1) Mature IDT of I4.0 and ASC; (2) Emerging IDT of I4.0 and ASC, and (3) A generic approach to the role and implications of IDT of I4.0 and ASC. This categorization gives an in-depth analysis of the relationship between the IDT of I4.0 and Agile Supply Chain and helps to clarify the way that the research has evolved. Among other findings, the results show that there is a prominent relationship between different types of IDT of I4.0 and ASC. These technologies can support the ASC by improving abilities to sense and respond to market changes and customer demands. The paper also discusses the gaps found in the literature, presents an ASC 4.0 model enabled by IDT of I4.0, and proposes new opportunities for future research.